Genetic and biochemical biomarkers in the macrophyte Bidens laevis L. exposed to a commercial formula of endosulfan - Pérez, Débora Jesabel (2014)
Previous studies in the wetland macrophyte Bidens laevis L have demonstrated that the insecticide endosulfan induces a high frequency of somatic chromosome aberrations in anaphase-telophase (CAAT) but no DNA changes as determined by the single cell gel electrophoresis (Comet) assay. Thus, cytogenetic biomarkers appear to be more sensitive to the toxic effects of the insecticide than the DNA molecule in the studied species. For this reason, the goals of this study were to use cytogenetic biomarkers-CAAT and abnormal metaphase-and defense biomarkers such as the activity of the antioxidant enzymes-guaiacol peroxidases (POD), glutathione reductase, and microsomal and cytosolic (m- and c-) glutathione-S-transferase (GST)-to evaluate in B. laevis effects caused by a commercial formulation of endosulfan. The frequency of CAAT was increased at 5, 10, 50, and 100 μg/L endosulfan with respect to the negative controls by 3.1, 2.5, 2.5, and 3.2-fold, respectively while the frequency of abnormal metaphases was also increased at the same concentrations by 3.5, 2.8, 3.2, and 11.3-fold, respectively. In addition to these aneugenic effects, other abnormalities such as C-mitosis and chromosome clumping were observed at 10 μg/L endosulfan. On the other hand, POD induction at 0.02, 0.5, 5, and 10 μg/L and m-GST inhibition at 0.5, 10, and 50 μg/L in plants exposed during 24 h to endosulfan were observed but all of these responses were highly variable. In conclusion, only cytogenetic biomarkers like CAAT in B. laevis can serve potentially as early warning systems to detect environmentally relevant concentrations of endosulfan in aquatic ecosystems.